Endogenous sialylation of the lipooligosaccharides of Neisseria meningitidis. - Mandrell, R E (1991)
Monoclonal antibodies (MAb) 3F11 and 06B4 recognize epitopes that are conserved on gonococcal lipooligosaccharides (LOS), present on some meningococcal LOS, and conserved on human erythrocytes. LOS of some group B and C prototype meningococcal LOS strains (LOS serotypes L1 to L8) treated with neuraminidase showed increased expression of the 3F11 and 06B4 MAb-defined epitopes. Neuraminidase-treated LOS separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and silver stained showed a shift in migration from a component with a mass of approximately 4.8 kDa to a component with a mass of between 4.5 and 4.6 kDa. The same strains grown in medium with excess CMP-N-acetylneuraminic acid had LOS that shifted in migration to a slightly higher component (mass, approximately 4.8 kDa). Chemical analysis of the neuraminidase-digested products from one LOS indicated it contained approximately 1.5% sialic acid. Covalent linkage between sialic acid and the LOS was confirmed by analysis of de-O-acylated and dephosphorylated LOS by liquid secondary ion mass spectrometry. Three studies show that some meningococci contain sialic acid in their LOS, that the sialic acid is cleaved and lost in conventional acetic acid hydrolysis, and that the sialic acid alters the expression of MAb-defined epitopes.